Place4Carers: a mixed-method study protocol for engaging family caregivers in meaningful actions for successful ageing in place. Issue 8 (11th August 2020) - Graffigna, Guendalina; Barello, Serena; Morelli, Niccolò; Gheduzzi, Eleonora; Corbo, Massimo; Ginex, Valeria; Ferrari, Roberta; Lascioli, Andrea; Feriti, Carolina; Masella, Cristina
Abstract : Introduction: Engaging family caregivers could be a critical asset to make the 'ageing-in-place' imperative a reality. This is particularly evident in rural and remote areas, where caregivers can fill the gaps that exist due to the fragmentation of the welfare system. However, there is little knowledge about the expectations that family caregivers have from healthcare services in rural and remote areas. Place4Carers (P4C) project aims to co-produce an innovative organisational model of social and healthcare services for family caregivers of older citizens living in Vallecamonica (Italy). The project is expected to facilitate ageing-in-place for older citizens, thus helping caregivers in their daily care activities. Methods and analysis: P4C is a community-based participatory research project featuring five work packages (WPs). WP1 consists of a survey of unmet needs of caregivers and older people receiving services in Vallecamonica. WP2 consists of a scoping literature review to map services that provide interventions of support to caregivers living in remote areas and promote engagement. WP3 organises co-creation workshops with caregivers to co-design, co-manage, and co-assess ideas and proposals for shaping caregiver-oriented services and organisational models. WP3 enriches the results of WP1 (survey) and WP2 (scoping literature review), and aims to co-create new ideas for intervention support with and for caregivers in relation to the objectives, features and characteristics of a new service able to address the caregivers' needs and expectations. WP4 tests the service ideas co-created in WP3 through piloting an intervention based on ideas co-created with caregivers. Finally, WP5 assesses the transferability of the intervention to other similar contexts. Ethics and dissemination: The study has been approved by the Ethics Committees of the Department of Psychology of Università Cattolica del Sacro Cuore and Politecnico of Milan. Results will be disseminated through peer-reviewed journals, scientific meetings and meetings with the general population.